Preparation method of visible light catalytic material for degrading dipterex sewage

By loading and converting it to a ferrosa fluoride-based polymer on the foamed copper matrix, the problem of low efficiency and insufficient stability of degrading dibasin sewage in the prior art is solved, and efficient and stable sewage treatment effect is achieved.

CN119951587APending Publication Date: 2025-05-09NORTH CHINA UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510115090.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

When existing visible photocatalytic materials degrade Dibaicheng organic phosphorus pesticide sewage, the catalytic degradation rate is low and the stability is insufficient, which limits the development of this technology.

Method used

An efficient visible photocatalytic material is formed by loading (Fe4F4)(SO4)4 compound on the surface of the foamed copper matrix and converting it into a ferrosa fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4]n.

Benefits of technology

It has achieved efficient visible photocatalytic degradation rate and excellent visible photocatalytic stability, which has significantly improved the effect of wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119951587A_ABST
    Figure CN119951587A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a visible light catalytic material for degrading dipterex sewage. The preparation method comprises the following steps: (1) loading a (Fe4F4) (SO4) 4 compound on the surface of a foamy copper matrix; (2) converting the (Fe4F4) (SO4) 4 compound loaded on the surface of the foamy copper matrix into (Fe4F4) (SO4) 4] [(Sm2F2) 4 (OH) 4; and (3) converting the (Fe4F4) (SO4) 4] [(Sm2F2) 4 (OH) 4 into the iron fluoride samarium coordination polymer [(Fe4F4) (C3H5N3) 4 (Sm2F2) 4] n. The visible light catalytic material prepared by the method disclosed by the invention has efficient visible light catalytic degradation rate of trichlorfon and excellent visible light catalytic stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of treatment of trichlorfon-containing sewage, in particular to a method for preparing a visible light catalytic material for degrading trichlorfon sewage. Background Art

[0002] Trichlorfon (O,O-dimethyl-(2,2,2-trichloro-1-hydroxyethyl)phosphonate) is a widely used organophosphorus insecticide. Trichlorfon can bind to the cholinesterase of pests, causing acetylcholine to accumulate in the pests, causing the pests' nervous system to malfunction and leading to poisoning and death; therefore, trichlorfon can be used to kill and control pests such as rice, wheat, forests, vegetables, and fish parasites. With the development of the economy, the amount and application range of trichlorfon organophosphorus insecticides are increasing. Trichlorfon's phosphate group can not only react with glutamate on the active site of acetylcholinesterase in humans and animals to cause excessive accumulation of acetylcholine, leading to the death of humans and animals, but also generate highly toxic dichlorvos under alkaline conditions. Because trichlorfon is soluble in water, trichlorfon organophosphorus insecticides have become serious pollutants in the current water environment, posing a serious threat to humans and the environment. Therefore, it is urgent to effectively treat trichlorfon wastewater.

[0003] The photocatalytic degradation of organic pollutants can photocatalytically degrade organic pollutants through a variety of active free radicals formed by photogenerated electrons and holes in photocatalytic materials. Photocatalytic degradation of trichlorfon organophosphorus pesticide wastewater is an effective way to treat it. However, the visible light catalytic degradation rate of catalytic materials for visible light catalytic degradation of trichlorfon organophosphorus pesticide wastewater is currently low, and its visible light catalytic stability needs to be improved, which has become a bottleneck restricting the development of visible light catalytic degradation technology for trichlorfon organophosphorus pesticide wastewater. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a visible light catalytic material for degrading trichlorfon wastewater. The visible light catalytic material prepared by the method has a high visible light catalytic degradation rate of trichlorfon and excellent visible light catalytic stability.

[0005] The technical solution adopted by the present invention to solve its technical problem is:

[0006] The present invention provides a method for preparing a visible light catalytic material for degrading trichlorfon wastewater, comprising the following steps:

[0007] Step [1]: loading (Fe4F4)(SO4)4 compound on the surface of the copper foam substrate;

[0008] Step [2] converting the (Fe4F4)(SO4)4 compound loaded on the surface of the copper foam substrate into (Fe4F4)(SO4)4][(Sm2F2)4(OH)4;

[0009] Step [3] Converting the (Fe4F4)(SO4)4][(Sm2F2)4(OH)4 into a samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n .

[0010] Preferably, the step [1] specifically includes the following operations:

[0011] a1. Ammonium fluoride, ferric chloride hexahydrate, ammonium persulfate, ferric sulfate and 98% concentrated sulfuric acid were added to deionized water and mixed to form a reaction solution A;

[0012] a2. Immerse the copper foam sample in reaction solution A, heat the water solution to 40-60°C, react for 8-14 hours, take out the copper foam sample, wash it with deionized water, and dry it at room temperature for 5-7 hours to obtain copper foam with (Fe4F4)(SO4)4 compound loaded on the surface, which is recorded as intermediate A.

[0013] Preferably, in step a1, the concentration of ammonium fluoride in the reaction solution A is 80 g / L-140 g / L, the concentration of ferric chloride hexahydrate is 30 g / L-50 g / L, the concentration of ammonium persulfate is 20 g / L-40 g / L, and the concentration of ferric sulfate is 50 g / L-80 g / L; and the amount of 98% concentrated sulfuric acid added per liter of the reaction solution A is 30 to 60 mL.

[0014] Preferably, in step a2, the weight of the copper foam immersed in each liter of the reaction solution A is 190-220 g.

[0015] Preferably, the step [2] specifically includes the following operations:

[0016] b1. Add samarium sulfate, sodium fluorosilicate, ammonium fluoride, urea and sodium hydroxide to deionized water and mix to form a reaction solution B;

[0017] b2. Immerse intermediate A in reaction solution B, heat the water solution to 50-70°C, react for 5-9 hours, take out the foam copper sample, wash it with deionized water, immerse it in dimethyl sulfoxide for 1-2 hours, and dry it at room temperature for 4-5 hours to obtain foam copper with (Fe4F4)(SO4)4][(Sm2F2)4(OH)4 loaded on the surface, which is recorded as intermediate B.

[0018] Preferably, in step b1, per liter of the reaction solution B, the amount of samarium sulfate added is 70-100 g, the amount of sodium fluorosilicate added is 5-10 g, the amount of ammonium fluoride added is 40-80 g, the amount of urea added is 20-40 g, and the amount of sodium hydroxide added is 30-70 g.

[0019] Preferably, in step b2, the weight of the intermediate A immersed in each liter of the reaction solution B is 110-130 g.

[0020] Preferably, the step [3] specifically includes the following operations:

[0021] c1. 1-methyl-1,2,4-triazole, 2-methoxy-3-(1-methyl-1H-1,2,4-triazole-3-yl)aniline and azobisisobutyronitrile were added to dimethyl sulfoxide and mixed to form a reaction solution C;

[0022] c2. Immerse the intermediate B in the reaction solution C, heat to 50-60°C, react for 96-120 hours, cool naturally to room temperature, take out the foam copper sample and wash it with acetone and deionized water to obtain a surface-loaded samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n The foam copper is the visible light catalytic material.

[0023] Preferably, in step c1, the amount of 1-methyl-1,2,4-triazole added to each liter of the reaction solution C is 80-140 mL, the amount of 2-methoxy-3-(1-methyl-1H-1,2,4-triazole-3-yl)aniline added is 30-60 g, and the amount of azobisisobutyronitrile added is 5-15 g.

[0024] Preferably, in step c2, the weight of the intermediate B immersed in each liter of the reaction solution C is 80-120 g.

[0025] The positive effect of the present invention is that the visible light catalytic material prepared by the method of the present invention has a samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] loaded on the surface of the foam copper. n The iron and fluorine of Fe4F4 are located at the vertices of two inverted tetrahedrons, and the samarium and fluorine of Sm2F2 are located at the four vertices of the planar quadrilateral; the two nitrogen atoms of 1-methyl-1,2,4-triazole form coordination bonds with the iron ion of Fe4F4 and the samarium ion of Sm2F2, respectively, thus forming [(Fe4F4)(C3H5N3)4(Sm2F2)4] nThe structural unit of the coordination polymer (Fe4F4)(C3H5N3)4(Sm2F2)4, the (Fe4F4)(C3H5N3)4(Sm2F2)4 structural unit forms a coordination bond with the nitrogen atom of the adjacent 1-methyl-1,2,4-triazole through the iron ion of Fe4F4 and the samarium ion of Sm2F2, forming a complex three-dimensional structure of iron fluoride samarium coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n Among them, the fluorine of Fe4F4 and Sm2F2 can produce charge transfer transition with 1-methyl-1,2,4-triazole, which is beneficial to improve the absorption efficiency of visible light; samarium and fluorine can effectively improve the spin-orbit coupling effect and promote the generation of photogenerated electrons. During the visible light irradiation process, the foam copper-based iron fluoride samarium coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n The electrons in the valence band are excited to the conduction band, and the photogenerated holes in the valence band react with the OH in the trichlorfon organophosphorus pesticide wastewater. - Form hydroxyl radical ·OH, O2 and photogenerated electrons form peroxyl radical ·O2 - , which can quickly and efficiently degrade trichlorfon in sewage.

[0026] In conclusion, the visible light photocatalytic material prepared according to the present invention has a highly efficient visible light photocatalytic degradation rate of trichlorfon and excellent visible light photocatalytic stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the preparation process of the visible light catalytic material of the present invention;

[0028] Figure 2 is a schematic diagram of the structure of the (Fe4F4)(SO4)4 compound of the present invention;

[0029] Figure 3 It is a schematic diagram of the structure of [(Fe4F4)(SO4)4][(Sm2F2)4(OH)4] of the present invention;

[0030] Figure 4 The iron samarium fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] of the present invention n Schematic diagram of the structure;

[0031] Figure 5 is a schematic diagram of the microstructure of the visible light catalytic material of the present invention;

[0032] Figure 6 The relative concentration of residual trichlorfon in the simulated trichlorfon-containing sewage photocatalytically degraded in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0033] Figure 7It is a relationship diagram between the number of times of use and the relative concentration of residual trichlorfon when Example 1, Comparative Example 1 and Comparative Example 2 are repeatedly used to treat simulated trichlorfon-containing sewage. DETAILED DESCRIPTION

[0034] Reference Figure 1 The present invention provides a method for preparing a visible light catalytic material for degrading trichlorfon wastewater, comprising the following steps:

[0035] Step [1] loading (Fe4F4)(SO4)4 compound on the surface of the copper foam substrate specifically comprises the following operations:

[0036] a1. ammonium fluoride, ferric chloride hexahydrate, ammonium persulfate, ferric sulfate and 98% concentrated sulfuric acid are added to deionized water and mixed to form a reaction solution A; wherein the concentration of ammonium fluoride in the reaction solution A is 80g / L-140g / L, the concentration of ferric chloride hexahydrate is 30g / L-50g / L, the concentration of ammonium persulfate is 20g / L-40g / L, and the concentration of ferric sulfate is 50g / L-80g / L; the amount of 98% concentrated sulfuric acid added per liter of the reaction solution A is 30 to 60mL.

[0037] a2. Immerse the copper foam sample in reaction solution A (the weight of the copper foam immersed in each liter of the reaction solution A is 190-220g), heat the water solution to 40-60°C, react for 8-14 hours, take out the copper foam sample, wash it with deionized water, and dry it at room temperature for 5-7 hours to obtain copper foam with (Fe4F4)(SO4)4 compound loaded on the surface, which is recorded as intermediate A. The structure of the (Fe4F4)(SO4)4 compound is as follows: Figure 2 shown.

[0038] Step [2] converts the (Fe4F4)(SO4)4 compound loaded on the surface of the copper foam substrate into (Fe4F4)(SO4)4][(Sm2F2)4(OH)4, specifically comprising the following operations:

[0039] b1. Add samarium sulfate, sodium fluorosilicate, ammonium fluoride, urea and sodium hydroxide to deionized water and mix to form a reaction solution B; wherein, per liter of the reaction solution B, the amount of samarium sulfate added is 70 to 100 g, the amount of sodium fluorosilicate added is 5 to 10 g, the amount of ammonium fluoride added is 40 to 80 g, the amount of urea added is 20 to 40 g, and the amount of sodium hydroxide added is 30 to 70 g.

[0040] b2. Immerse the intermediate A in the reaction solution B (the weight of the intermediate A immersed in each liter of the reaction solution B is 110-130g), heat the water solution to 50-70°C, react for 5-9 hours, take out the foam copper sample, wash it with deionized water, immerse it in dimethyl sulfoxide for 1-2 hours, and dry it at room temperature for 4-5 hours to obtain a foam copper with (Fe4F4)(SO4)4][(Sm2F2)4(OH)4 loaded on the surface, which is recorded as intermediate B. The structure of the (Fe4F4)(SO4)4][(Sm2F2)4(OH)4 is as follows Figure 3 shown.

[0041] Step [3] Converting the (Fe4F4)(SO4)4][(Sm2F2)4(OH)4 into a samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n , including the following operations:

[0042] c1. Add 1-methyl-1,2,4-triazole, 2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)aniline and azobisisobutyronitrile to dimethyl sulfoxide and mix to form a reaction solution C; wherein, per liter of the reaction solution C, the amount of 1-methyl-1,2,4-triazole added is 80 to 140 mL, the amount of 2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)aniline added is 30 to 60 g, and the amount of azobisisobutyronitrile added is 5 to 15 g.

[0043] c2. The intermediate B is immersed in the reaction solution C (the weight of the intermediate B immersed in each liter of the reaction solution C is 80-120g), heated to 50-60°C, reacted for 96-120 hours, cooled naturally to room temperature, and the foam copper sample is taken out and washed with acetone and deionized water to obtain a surface-loaded samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n The foam copper is the visible light catalytic material, and its microstructure diagram is as shown in Figure 5 Wherein, the samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n The structure of Figure 4 shown.

[0044] The preferred embodiments of the present invention are described below by way of example.

[0045] Example 1

[0046] Preferred embodiment 1 of the present invention provides a method for preparing a visible light catalytic material for degrading trichlorfon wastewater, comprising the following steps:

[0047] Step [1] loading (Fe4F4)(SO4)4 compound on the surface of the copper foam substrate specifically comprises the following operations:

[0048] a1. Ammonium fluoride, ferric chloride hexahydrate, ammonium persulfate, ferric sulfate and 98% concentrated sulfuric acid are added to deionized water and mixed to form a reaction solution A; wherein the concentration of ammonium fluoride in the reaction solution A is 120 g / L, the concentration of ferric chloride hexahydrate is 40 g / L, the concentration of ammonium persulfate is 30 g / L, and the concentration of ferric sulfate is 60 g / L; the amount of 98% concentrated sulfuric acid added per liter of the reaction solution A is 50 mL.

[0049] a2. Immerse the foam copper sample in reaction solution A (the weight of the foam copper immersed in each liter of the reaction solution A is 195 g), heat the water solution to 50°C, react for 10 hours, take out the foam copper sample, wash it with deionized water, and dry it at room temperature for 6 hours to obtain foam copper with (Fe4F4)(SO4)4 compound loaded on the surface, which is recorded as intermediate A.

[0050] Step [2] converts the (Fe4F4)(SO4)4 compound loaded on the surface of the copper foam substrate into (Fe4F4)(SO4)4][(Sm2F2)4(OH)4, specifically comprising the following operations:

[0051] b1. Add samarium sulfate, sodium fluorosilicate, ammonium fluoride, urea and sodium hydroxide to deionized water and mix to form a reaction solution B; wherein, per liter of the reaction solution B, the amount of samarium sulfate added is 80 g, the amount of sodium fluorosilicate added is 8 g, the amount of ammonium fluoride added is 70 g, the amount of urea added is 30 g, and the amount of sodium hydroxide added is 60 g.

[0052] b2. Immerse intermediate A in reaction solution B (the weight of intermediate A immersed in each liter of reaction solution B is 115 g), heat the water solution to 60°C, react for 6 hours, take out the foam copper sample, wash it with deionized water, immerse it in dimethyl sulfoxide for 2 hours, and dry it at room temperature for 5 hours to obtain foam copper with surface loaded with (Fe4F4)(SO4)4][(Sm2F2)4(OH)4, which is recorded as intermediate B.

[0053] Step [3] Converting the (Fe4F4)(SO4)4][(Sm2F2)4(OH)4 into a samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n , including the following operations:

[0054] c1. Add 1-methyl-1,2,4-triazole, 2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)aniline and azobisisobutyronitrile to dimethyl sulfoxide and mix to form a reaction solution C; wherein, per liter of the reaction solution C, the amount of 1-methyl-1,2,4-triazole added is 130 mL, the amount of 2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)aniline added is 40 g, and the amount of azobisisobutyronitrile added is 12 g.

[0055] c2. The intermediate B was immersed in the reaction solution C (the weight of the intermediate B immersed in each liter of the reaction solution C was 110 g), heated to 58°C, reacted for 110 hours, and naturally cooled to room temperature. The foam copper sample was taken out and washed with acetone and deionized water to obtain a surface-loaded samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n The foam copper is the visible light catalytic material, which is recorded as Example 1.

[0056] Comparative Example 1

[0057] This comparative example 1 provides a method for preparing a visible light catalytic material for degrading trichlorfon wastewater, comprising the following steps:

[0058] Step [1] loading (Fe4F4)(SO4)4 compound on the surface of the copper foam substrate specifically comprises the following operations:

[0059] a1. ammonium fluoride, ferric chloride hexahydrate, ammonium persulfate, ferric sulfate and 98% concentrated sulfuric acid are added to deionized water and mixed to form a reaction solution A; wherein the concentration of ammonium fluoride in the reaction solution A is 90 g / L, the concentration of ferric chloride hexahydrate is 40 g / L, the concentration of ammonium persulfate is 30 g / L, and the concentration of ferric sulfate is 60 g / L; the amount of 98% concentrated sulfuric acid added per liter of the reaction solution A is 40 mL.

[0060] a2. Immerse the foam copper sample in reaction solution A (the weight of the foam copper immersed in each liter of the reaction solution A is 210 g), heat the water solution to 50°C, react for 10 hours, take out the foam copper sample, wash it with deionized water, and dry it at room temperature for 6 hours to obtain foam copper with (Fe4F4)(SO4)4 compound loaded on the surface, which is recorded as intermediate A.

[0061] Step [2] Converting the (Fe4F4)(SO4)4 compound loaded on the surface of the copper foam substrate into an iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4] n , including the following operations:

[0062] c1. Add 1-methyl-1,2,4-triazole, 2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)aniline and azobisisobutyronitrile to dimethyl sulfoxide and mix to form a reaction solution C; wherein, per liter of the reaction solution C, the amount of 1-methyl-1,2,4-triazole added is 90 mL, the amount of 2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)aniline added is 40 g, and the amount of azobisisobutyronitrile added is 10 g.

[0063] c2. The intermediate A was immersed in the reaction solution C (the weight of the intermediate A immersed in each liter of the reaction solution C was 90 g), heated to 55°C, reacted for 100 hours, and naturally cooled to room temperature. The foam copper sample was taken out and washed with acetone and deionized water to obtain a surface-loaded iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4] n The foam copper is recorded as Comparative Example 1.

[0064] Comparative Example 2

[0065] This comparative example 2 provides a method for preparing a visible light catalytic material for degrading trichlorfon wastewater, comprising the following steps:

[0066] Step [1] loading (Fe4F4)(SO4)4 compound on the surface of the copper foam substrate specifically comprises the following operations:

[0067] a1. Ammonium fluoride, ferric chloride hexahydrate, ammonium persulfate, ferric sulfate and 98% concentrated sulfuric acid are added to deionized water and mixed to form a reaction solution A; wherein the concentration of ammonium fluoride in the reaction solution A is 100 g / L, the concentration of ferric chloride hexahydrate is 35 g / L, the concentration of ammonium persulfate is 25 g / L, and the concentration of ferric sulfate is 70 g / L; the amount of 98% concentrated sulfuric acid added per liter of the reaction solution A is 50 mL.

[0068] a2. Immerse the foam copper sample in reaction solution A (the weight of the foam copper immersed in each liter of the reaction solution A is 190-220 g), heat the water solution to 40-60°C, react for 8-14 hours, take out the foam copper sample, wash it with deionized water, and dry it at room temperature for 5-7 hours to obtain foam copper with (Fe4F4)(SO4)4 compound loaded on the surface, which is recorded as intermediate A.

[0069] Step [2] converts the (Fe4F4)(SO4)4 compound loaded on the surface of the copper foam substrate into (Fe4F4)(SO4)4][(Sm2F2)4(OH)4, specifically comprising the following operations:

[0070] b1. Add samarium sulfate, sodium fluorosilicate, ammonium fluoride, urea and sodium hydroxide to deionized water and mix to form a reaction solution B; wherein, per liter of the reaction solution B, the amount of samarium sulfate added is 80 g, the amount of sodium fluorosilicate added is 6 g, the amount of ammonium fluoride added is 70 g, the amount of urea added is 25 g, and the amount of sodium hydroxide added is 50 g.

[0071] b2. The intermediate A is immersed in the reaction solution B (the weight of the intermediate A immersed in each liter of the reaction solution B is 120 g), the water solution is heated to 55°C, and the reaction is carried out for 6 hours. The foam copper sample is taken out, washed with deionized water, immersed in dimethyl sulfoxide for 1.5 hours, and dried at room temperature for 4 hours to obtain a foam copper with a surface load of (Fe4F4)(SO4)4][(Sm2F2)4(OH)4, which is recorded as Comparative Example 2.

[0072] In order to analyze the degradation rate of the visible light catalytic degradation of trichlorfon sewage in Example 1, Comparative Example 1 and Comparative Example 2 and its visible light catalytic stability, trichlorfon organophosphorus pesticide was added to deionized water to form simulated trichlorfon-containing sewage with a trichlorfon organophosphorus pesticide concentration of 15 mg / L. 100 ml of simulated trichlorfon-containing sewage was poured into beakers, and 5 g of Example 1, Comparative Example 1 and Comparative Example 2 were placed in beakers respectively. The simulated trichlorfon sewage was degraded by light irradiation with 100W and 200W xenon lamp light sources under visible light with a wavelength of 450nm for 90 minutes, and the inorganic phosphorus concentration of trichlorfon decomposed during the visible light catalytic degradation process was determined by molybdenum blue colorimetry. The visible light catalytic degradation rate of the trichlorfon organophosphorus pesticide was obtained according to the ratio of the inorganic phosphorus content to the initial organic phosphorus content, thereby obtaining the relative concentration of residual trichlorfon. The results are as follows: Figure 6 As shown in the figure, it can be seen that the relative concentrations of residual trichlorfon degraded by visible light catalytic degradation under the conditions of 100W and 200W xenon lamps simulating visible light in Example 1 are only 0.08 and 0.05, respectively, while under the same conditions, the relative concentrations of residual trichlorfon in Comparative Example 1 are 0.35 and 0.31, respectively, and the relative concentrations of residual trichlorfon in Comparative Example 2 are as high as 0.63 and 0.48.

[0073] Under the aforementioned 200W xenon lamp simulated visible light irradiation condition for 90 minutes, Example 1, Comparative Example 1 and Comparative Example 2 were used repeatedly to treat the simulated trichlorfon sewage. The relationship between the number of times of use and the relative concentration of residual trichlorfon was as follows: Figure 7 As shown in the figure, it can be seen that the relative concentration of residual trichlorfon in Example 1 after visible light catalytic degradation of simulated trichlorfon wastewater with a concentration of 15 mg / L when recycled for the tenth time is only 0.1, which is much lower than the relative concentration of residual trichlorfon in Comparative Example 1 and Comparative Example 2 when recycled for the tenth time (0.69 and 0.86, respectively). Obviously, Example 1 has stable and efficient recyclable characteristics.

[0074] In summary, the visible light photocatalytic material prepared according to the present invention has a highly efficient visible light photocatalytic degradation rate of trichlorfon and excellent visible light photocatalytic stability.

[0075] To illustrate in further detail, three additional examples are provided below.

[0076] Example 2

[0077] Preferred embodiment 2 of the present invention provides a method for preparing a visible light catalytic material for degrading trichlorfon wastewater, comprising the following steps:

[0078] Step [1] loading (Fe4F4)(SO4)4 compound on the surface of the copper foam substrate specifically comprises the following operations:

[0079] a1. Ammonium fluoride, ferric chloride hexahydrate, ammonium persulfate, ferric sulfate and 98% concentrated sulfuric acid are added to deionized water and mixed to form a reaction solution A; wherein the concentration of ammonium fluoride in the reaction solution A is 80 g / L, the concentration of ferric chloride hexahydrate is 50 g / L, the concentration of ammonium persulfate is 20 g / L, and the concentration of ferric sulfate is 50 g / L; the amount of 98% concentrated sulfuric acid added per liter of the reaction solution A is 60 mL.

[0080] a2. Immerse the foam copper sample in reaction solution A (the weight of the foam copper immersed in each liter of the reaction solution A is 190 g), heat the water solution to 40°C, react for 14 hours, take out the foam copper sample, wash it with deionized water, and dry it at room temperature for 5 hours to obtain foam copper with (Fe4F4)(SO4)4 compound loaded on the surface, which is recorded as intermediate A.

[0081] Step [2] converts the (Fe4F4)(SO4)4 compound loaded on the surface of the copper foam substrate into (Fe4F4)(SO4)4][(Sm2F2)4(OH)4, specifically comprising the following operations:

[0082] b1. Add samarium sulfate, sodium fluorosilicate, ammonium fluoride, urea and sodium hydroxide to deionized water and mix to form a reaction solution B; wherein, per liter of the reaction solution B, the amount of samarium sulfate added is 70 g, the amount of sodium fluorosilicate added is 5 g, the amount of ammonium fluoride added is 40 g, the amount of urea added is 40 g, and the amount of sodium hydroxide added is 30 g.

[0083] b2. Immerse intermediate A in reaction solution B (the weight of intermediate A immersed in each liter of reaction solution B is 110 g), heat the water solution to 50°C, react for 9 hours, take out the foam copper sample, wash it with deionized water, immerse it in dimethyl sulfoxide for 1 hour, and dry it at room temperature for 4 hours to obtain foam copper with surface loaded with (Fe4F4)(SO4)4][(Sm2F2)4(OH)4, which is recorded as intermediate B.

[0084] Step [3] Converting the (Fe4F4)(SO4)4][(Sm2F2)4(OH)4 into a samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n , including the following operations:

[0085] c1. Add 1-methyl-1,2,4-triazole, 2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)aniline and azobisisobutyronitrile to dimethyl sulfoxide and mix to form a reaction solution C; wherein, per liter of the reaction solution C, the amount of 1-methyl-1,2,4-triazole added is 80 mL, the amount of 2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)aniline added is 30 g, and the amount of azobisisobutyronitrile added is 5 g.

[0086] c2. The intermediate B was immersed in the reaction solution C (the weight of the intermediate B immersed in each liter of the reaction solution C was 80 g), heated to 50°C, reacted for 120 hours, and naturally cooled to room temperature. The foam copper sample was taken out and washed with acetone and deionized water to obtain a surface-loaded samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n The foam copper is the visible light catalytic material.

[0087] Example 3

[0088] Preferred embodiment 3 of the present invention provides a method for preparing a visible light catalytic material for degrading trichlorfon wastewater, comprising the following steps:

[0089] Step [1] loading (Fe4F4)(SO4)4 compound on the surface of the copper foam substrate specifically comprises the following operations:

[0090] a1. Ammonium fluoride, ferric chloride hexahydrate, ammonium persulfate, ferric sulfate and 98% concentrated sulfuric acid are added to deionized water and mixed to form a reaction solution A; wherein the concentration of ammonium fluoride in the reaction solution A is 140 g / L, the concentration of ferric chloride hexahydrate is 30 g / L, the concentration of ammonium persulfate is 20 g / L, and the concentration of ferric sulfate is 80 g / L; the amount of 98% concentrated sulfuric acid added per liter of the reaction solution A is 30 mL.

[0091] a2. The foam copper sample was immersed in reaction solution A (the weight of the foam copper immersed in each liter of the reaction solution A was 220 g), the water solution was heated to 60°C, and the reaction was carried out for 8 hours. The foam copper sample was taken out, washed with deionized water, and dried at room temperature for 7 hours to obtain a foam copper with a (Fe4F4)(SO4)4 compound loaded on the surface, which was recorded as intermediate A.

[0092] Step [2] converts the (Fe4F4)(SO4)4 compound loaded on the surface of the copper foam substrate into (Fe4F4)(SO4)4][(Sm2F2)4(OH)4, specifically comprising the following operations:

[0093] b1. Add samarium sulfate, sodium fluorosilicate, ammonium fluoride, urea and sodium hydroxide to deionized water and mix to form a reaction solution B; wherein, per liter of the reaction solution B, the amount of samarium sulfate added is 100 g, the amount of sodium fluorosilicate added is 10 g, the amount of ammonium fluoride added is 80 g, the amount of urea added is 20 g, and the amount of sodium hydroxide added is 70 g.

[0094] b2. Immerse intermediate A in reaction solution B (the weight of intermediate A immersed in each liter of reaction solution B is 130 g), heat the water solution to 70°C, react for 5 hours, take out the foam copper sample, wash it with deionized water, immerse it in dimethyl sulfoxide for 2 hours, and dry it at room temperature for 5 hours to obtain foam copper with surface loaded with (Fe4F4)(SO4)4][(Sm2F2)4(OH)4, which is recorded as intermediate B.

[0095] Step [3] Converting the (Fe4F4)(SO4)4][(Sm2F2)4(OH)4 into a samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n , including the following operations:

[0096] c1. Add 1-methyl-1,2,4-triazole, 2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)aniline and azobisisobutyronitrile to dimethyl sulfoxide and mix to form a reaction solution C; wherein, per liter of the reaction solution C, the amount of 1-methyl-1,2,4-triazole added is 140 mL, the amount of 2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)aniline added is 60 g, and the amount of azobisisobutyronitrile added is 15 g.

[0097] c2. The intermediate B was immersed in the reaction solution C (the weight of the intermediate B immersed in each liter of the reaction solution C was 120 g), heated to 60°C, reacted for 96 hours, and naturally cooled to room temperature. The foam copper sample was taken out and washed with acetone and deionized water to obtain a surface-loaded samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n The foam copper is the visible light catalytic material.

[0098] Example 4

[0099] Preferred embodiment 4 of the present invention provides a method for preparing a visible light catalytic material for degrading trichlorfon wastewater, comprising the following steps:

[0100] Step [1] loading (Fe4F4)(SO4)4 compound on the surface of the copper foam substrate specifically comprises the following operations:

[0101] a1. Ammonium fluoride, ferric chloride hexahydrate, ammonium persulfate, ferric sulfate and 98% concentrated sulfuric acid are added to deionized water and mixed to form a reaction solution A; wherein the concentration of ammonium fluoride in the reaction solution A is 110 g / L, the concentration of ferric chloride hexahydrate is 40 g / L, the concentration of ammonium persulfate is 30 g / L, and the concentration of ferric sulfate is 65 g / L; the amount of 98% concentrated sulfuric acid added per liter of the reaction solution A is 45 mL.

[0102] a2. The foam copper sample was immersed in reaction solution A (the weight of the foam copper immersed in each liter of the reaction solution A was 205 g), the water solution was heated to 50°C, and the reaction was carried out for 11 hours. The foam copper sample was taken out, washed with deionized water, and dried at room temperature for 6 hours to obtain a foam copper with a (Fe4F4)(SO4)4 compound loaded on the surface, which was recorded as intermediate A.

[0103] Step [2] converts the (Fe4F4)(SO4)4 compound loaded on the surface of the copper foam substrate into (Fe4F4)(SO4)4][(Sm2F2)4(OH)4, specifically comprising the following operations:

[0104] b1. Add samarium sulfate, sodium fluorosilicate, ammonium fluoride, urea and sodium hydroxide to deionized water and mix to form a reaction solution B; wherein, per liter of the reaction solution B, the amount of samarium sulfate added is 85 g, the amount of sodium fluorosilicate added is 7.5 g, the amount of ammonium fluoride added is 60 g, the amount of urea added is 30 g, and the amount of sodium hydroxide added is 50 g.

[0105] b2. Immerse intermediate A in reaction solution B (the weight of intermediate A immersed in each liter of reaction solution B is 120 g), heat the water solution to 60°C, react for 7 hours, take out the foam copper sample, wash it with deionized water, immerse it in dimethyl sulfoxide for 1.5 hours, and dry it at room temperature for 4.5 hours to obtain foam copper with surface loaded with (Fe4F4)(SO4)4][(Sm2F2)4(OH)4, which is recorded as intermediate B.

[0106] Step [3] Converting the (Fe4F4)(SO4)4][(Sm2F2)4(OH)4 into a samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n , including the following operations:

[0107] c1. Add 1-methyl-1,2,4-triazole, 2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)aniline and azobisisobutyronitrile to dimethyl sulfoxide and mix to form a reaction solution C; wherein, per liter of the reaction solution C, the amount of 1-methyl-1,2,4-triazole added is 110 mL, the amount of 2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)aniline added is 45 g, and the amount of azobisisobutyronitrile added is 10 g.

[0108] c2. The intermediate B was immersed in the reaction solution C (the weight of the intermediate B immersed in each liter of the reaction solution C was 100 g), heated to 55°C, reacted for 108 hours, and naturally cooled to room temperature. The foam copper sample was taken out and washed with acetone and deionized water to obtain a surface-loaded samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n The foam copper is the visible light catalytic material.

[0109] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a visible light catalytic material for degrading trichlorfon wastewater, characterized in that: The following steps are included: Step [1] Loading (Fe4F4)(SO4)4 compound on the surface of the copper foam substrate; Step [2] converting the (Fe4F4)(SO4)4 compound loaded on the surface of the copper foam substrate into (Fe4F4)(SO4)4][(Sm2F2)4(OH)4; Step [3] Converting the (Fe4F4)(SO4)4][(Sm2F2)4(OH)4 into a samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n .

2. The method for preparing a visible light catalytic material for degrading trichlorfon wastewater according to claim 1, characterized in that: The step [1] specifically includes the following operations: a1. Ammonium fluoride, ferric chloride hexahydrate, ammonium persulfate, ferric sulfate and 98% concentrated sulfuric acid were added to deionized water and mixed to form a reaction solution A; a2. Immerse the copper foam sample in reaction solution A, heat the water solution to 40-60°C, react for 8-14 hours, take out the copper foam sample, wash it with deionized water, and dry it at room temperature for 5-7 hours to obtain copper foam with (Fe4F4)(SO4)4 compound loaded on the surface, which is recorded as intermediate A.

3. The method for preparing a visible light catalytic material for degrading trichlorfon wastewater according to claim 2, characterized in that: In step a1, the concentration of ammonium fluoride in the reaction solution A is 80g / L-140g / L, the concentration of ferric chloride hexahydrate is 30g / L-50g / L, the concentration of ammonium persulfate is 20g / L-40g / L, and the concentration of ferric sulfate is 50g / L-80g / L; the amount of 98% concentrated sulfuric acid added per liter of the reaction solution A is 30-60mL.

4. The method for preparing a visible light catalytic material for degrading trichlorfon wastewater according to claim 2, characterized in that: In step a2, the weight of the foam copper immersed in each liter of the reaction solution A is 190-220 g.

5. The method for preparing a visible light catalytic material for degrading trichlorfon wastewater according to claim 1, characterized in that: The step [2] specifically includes the following operations: b1. Add samarium sulfate, sodium fluorosilicate, ammonium fluoride, urea and sodium hydroxide to deionized water and mix to form a reaction solution B; b2. Immerse intermediate A in reaction solution B, heat the water solution to 50-70°C, react for 5-9 hours, take out the foam copper sample, wash it with deionized water, immerse it in dimethyl sulfoxide for 1-2 hours, and dry it at room temperature for 4-5 hours to obtain foam copper with (Fe4F4)(SO4)4][(Sm2F2)4(OH)4 loaded on the surface, which is recorded as intermediate B.

6. The method for preparing a visible light catalytic material for degrading trichlorfon wastewater according to claim 5, characterized in that: In step b1, per liter of the reaction solution B, the amount of samarium sulfate added is 70-100 g, the amount of sodium fluorosilicate added is 5-10 g, the amount of ammonium fluoride added is 40-80 g, the amount of urea added is 20-40 g, and the amount of sodium hydroxide added is 30-70 g.

7. The method for preparing a visible light catalytic material for degrading trichlorfon wastewater according to claim 5, characterized in that: In step b2, the weight of the intermediate A immersed in each liter of the reaction solution B is 110-130 g.

8. The method for preparing a visible light catalytic material for degrading trichlorfon wastewater according to claim 1, characterized in that: The step [3] specifically includes the following operations: c1. 1-methyl-1,2,4-triazole, 2-methoxy-3-(1-methyl-1H-1,2,4-triazole-3-yl)aniline and azobisisobutyronitrile were added to dimethyl sulfoxide and mixed to form a reaction solution C; c2. Immerse the intermediate B in the reaction solution C, heat to 50-60°C, react for 96-120 hours, cool naturally to room temperature, take out the foam copper sample and wash it with acetone and deionized water to obtain a surface-loaded samarium iron fluoride coordination polymer [(Fe4F4)(C3H5N3)4(Sm2F2)4] n The foam copper is the visible light catalytic material.

9. The method for preparing a visible light catalytic material for degrading trichlorfon wastewater according to claim 8, characterized in that: In step c1, the amount of 1-methyl-1,2,4-triazole added to each liter of the reaction solution C is 80-140 mL, the amount of 2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)aniline added is 30-60 g, and the amount of azobisisobutyronitrile added is 5-15 g.

10. The method for preparing a visible light catalytic material for degrading trichlorfon wastewater according to claim 8, characterized in that: In step c2, the weight of the intermediate B immersed in each liter of the reaction solution C is 80-120 g.